The Dynamics of Innovation on Firm Performance: Empirical Analysis of Pharmaceutical Manufacturing Firms in Sindh Pakistan - Raza, Saleem; Laghari, Minhoon Khan; Junejo, Mummtaz Ali (Pakistan Journal of Humanities and Social Sciences, 2023)
Innovation is defined as the process of producing developing new products and services for significant positive change, innovation is a crucial driver of economic growth and societal progress. Aim of this paper is to analyze the direct, indirect, and total effects of exogenous variables product innovation, process innovation, and organizational innovation, with the mediating effects of organizational innovation capability and dynamic capability on endogenous variable firm performance. In the context of Resource Based view theory organizational achievement is defined with reference to utilization resources, proficiencies to achieve competitive advantage, sustainable and viable. In the framework of this concepts, innovation which leads to shape resources capabilities for better performance in pharmaceutical manufacturing firms of Sindh. Path analysis approach is incorporated for analyzing multivariate causal effect, a five-point Likert scale, and a pretested, closed ended questionnaire was used for feedback of responses. Cluster sampling technique is incorporated for compilation of data, by using SPSS 25 version software for demographic statistics, and PLS 3.5.V for inferential statistics. Direct, indirect, and total effects is significantly positive, except PI > to DC > is insignificantly associated with firm performance. Partial mediation is established by the, product innovation, and organizational innovation through organization innovation capability and dynamic capability with firm performance.The limitation only cover the pharmaceutical manufacturing firms al so limitations are expelled various variables of firm performance because of limited time. Beside these limitations, this study provides direction to top management and policymakers for enhancing of performance of manufacturing firms of Sindh.